Village Youth Participation in Educating to Prevent the Spread of Covid-19 - Ali Alamsyah Kusumadinata; Miftakhul Rizky Maulida; Astrid Sri Wahyuni Sumah (Formosa Journal of Science and Technology, 2022)
Community participation is certainly needed to reduce the spread of Covid-19, especially the participation of youth as agents of change. Various participations can be carried out to reduce the spread of Covid-19, one of which is by educating the public about Covid-19. The purpose of this study is to determine youth participation in educating the people of Cadasngampar Village regarding preventing the spread of Covid-19. This study uses a descriptive qualitative approach. Data obtained using interview techniques, observation, and documentation. The results of the study show that youth participation in educating the prevention of the spread of Covid-19 in Cadasngampar Village is by persuasively reminding and inviting the community to keep updating information and to prevent crowds and comply with health protocols in the village. Activities involving village organization al. Karang Taruna Mekar Jaya with the aim of increasing village community awareness about the importance of wearing masks and looking after each other in the village environment.